2009
DOI: 10.1016/j.jhep.2008.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Sustained JNK1 activation is associated with altered histone H3 methylations in human liver cancer

Abstract: Background/Aims Aberrant c-Jun N-terminal kinase (JNK) activation has been linked to hepatocellular carcinoma (HCC) in mouse models. It remains unclear whether JNK activation plays an important role in human HCC and, if so, how JNK signaling contributes to the initiation or progression of HCC. Methods The JNK activation, global gene expression, and the status of histone H3 methylations were measured in 31 primary human hepatocellular carcinoma (HCC) samples paired with the adjacent non-cancerous (ANC) tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 52 publications
(58 reference statements)
6
96
0
Order By: Relevance
“…Over half of human HCC samples show over-activated JNK1 (Hui et al, 2008). Sustained JNK1 expression in human HCC contributes to altered histone H3 methylation, which enhances the expression of genes regulating cell growth (Chang et al, 2009). Using inflammation-associated mouse HCC models, it was confirmed that JNK1 promotes tumor cell proliferation, probably due to the elevated expression of the cell cycle inhibitor p21 and the reduced expression of c-Myc (Hui et al, 2008).…”
Section: Jnks In Inflammation and Cancermentioning
confidence: 99%
“…Over half of human HCC samples show over-activated JNK1 (Hui et al, 2008). Sustained JNK1 expression in human HCC contributes to altered histone H3 methylation, which enhances the expression of genes regulating cell growth (Chang et al, 2009). Using inflammation-associated mouse HCC models, it was confirmed that JNK1 promotes tumor cell proliferation, probably due to the elevated expression of the cell cycle inhibitor p21 and the reduced expression of c-Myc (Hui et al, 2008).…”
Section: Jnks In Inflammation and Cancermentioning
confidence: 99%
“…In recent years, studies have shed light on the clinical implications of signalling pathways in HCC, including the Ras/Raf/MEK/ERK pathway [16] , the PI3K/Akt/mTOR pathway [17] , the JNK pathway [18] and the NF-κB pathway [19] . A promising approach would be to identify molecular pathways responsible for initiating and sustaining HCC as targets for HCC therapy.…”
Section: Hepatocellular Carcinoma and The Unmet Medical Needsmentioning
confidence: 99%
“…128,129 More recently, definitive evidence has revealed a significant relationship between sustained JNK activation and the development of HCC. [129][130][131][132] JNK1 is overactivated in more than 50% of human HCC samples. [129][130][131][132] In one study, 56% of HCC tissue samples demonstrated elevated JNK1 activity relative to the case-matched noncancerous liver tissue.…”
mentioning
confidence: 99%
“…[129][130][131][132] JNK1 is overactivated in more than 50% of human HCC samples. [129][130][131][132] In one study, 56% of HCC tissue samples demonstrated elevated JNK1 activity relative to the case-matched noncancerous liver tissue. 131 This finding was supported by immunoblotting studies which demonstrated highly active JNK1 in about 55% of human HCC samples.…”
mentioning
confidence: 99%